Research on Load Stress in Bottom of Ultra-short Flexsplines of Harmonic Drives - Li Yifu; Chen Xiaoxia; Xing Jingzhong; Chen Liang (Jixie chuandong)
In order to reveal the stress distribution law of a bottom of the ultra-short flexspline under load, a theoretical calculation method of the load equivalent stress of the bottom of the flexspline is proposed. The flexural and symmetrical deformation model of flexural cylinder under the action of wave generator is established, and the flexural normal stress and shear stress caused by assembly deformation and shear stress under the load torque are solved. Based on the Mises yield criterion, the theoretical expression of the load equivalent stress at the bottom of the flexspline is obtained. The finite element model is established and the theoretical solutions of the assembly and load stress at the bottom of the flexspline are verified numerically. The results show that the bending radial normal stress is the main stress of the assembly stress at the bottom of the flexspline cylinder; the maximum shear stress at the bottom of the flexspline under the rated torque is at 45°; with the increase of the load torque, the maximum shear stress gradually passes to the fixed end, and the equivalent stress is evenly distributed at the fixed end. The shear stress at the maximum instantaneous allowable torque is the principal stress of the equivalent stress at the bottom of the flexspline, which provides guidance for the strength design of the bottom of the flexspline.